2017
DOI: 10.2495/sdp170471
|View full text |Cite
|
Sign up to set email alerts
|

Retardation Effect on Thermally-Modified Spruce Wood

Abstract: The subject matter of this paper is spruce wood (Picea abies L.). The thermal treatment of wood (thermal wood) is a new technology of wood treatment, improving its physical and biological properties and increasing its resistance to biological wood-destroying agents and atmospheric effects. Its fire and technical properties, capability to set it on fire and burn it have been studied less. Research in the aforementioned subject is the subject matter of this paper, together with an option to treat this thermally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Result shows that the weight loss rate decrease with an increase in heat temperature especially beech and oak woods. Osvaldová and Gaff [25] studied that different thermal modifications and the influence of fire retardant on combustion properties of thermally modified spruce (Picea abies L.) wood. They reported that the highest burning rate has been reached with heat-treated samples at 210°C.…”
Section: Resultsmentioning
confidence: 99%
“…Result shows that the weight loss rate decrease with an increase in heat temperature especially beech and oak woods. Osvaldová and Gaff [25] studied that different thermal modifications and the influence of fire retardant on combustion properties of thermally modified spruce (Picea abies L.) wood. They reported that the highest burning rate has been reached with heat-treated samples at 210°C.…”
Section: Resultsmentioning
confidence: 99%
“…Surface treatment of the boards was performed by planing (with a combined woodworking machine Woodster C6 06, Woodster GmbH, Ichenhausen, Germany). Surface roughness is one of the factors influencing the ignition of samples [42]. The average density of the tested spruce wood samples was 422.9 kg•m −3 and beech wood was 697.2 kg•m −3 .…”
Section: Parametersmentioning
confidence: 99%
“…Test results showed that heat treatment showed positive effects on the fire safety of Larix wood, weakening the intensity of its combustion properties and also reducing the ignition time. Osvaldová and Gaff [33] determined retardation effect on heat-treated spruce wood. They reported that, heat-treated fire retardant treated samples have lower weight losses than non-treated samples.…”
Section: Statistical Analysesmentioning
confidence: 99%